Singkawang City Government’s Strategy to Increase Knowledge Dimension of The Human Development Index (HDI) in 2023 - Millavathiy, Riri; Muradi, Muradi; Mulyawan, Rahman (Publik : (Jurnal Ilmu Administrasi), 2025)
Singkawang Mayor's Regulation Number 11.1 of 2023 concerning Changes to the Singkawang City Regional Development Plan for 2023 - 2026 with one of the objectives being "Increasing the quality of competitive and characterful human resources" with the strategic target "Increasing the quality of Education" providing direction for Education policy, especially in efforts to increase the knowledge dimension of HDI.The low increase in indicators in the knowledge dimension means that breakthrough efforts and appropriate local government strategies are needed to encourage the increase in HLS and RLS. research with the title Singkawang City Government Strategy in Increasing the Human Development Index (HDI) in the Knowledge Dimension in 2023 with strategy theory from Geoff Mulgan (2009) to analyze the Singkawang City Government's strategy in increasing the Human Development Index (HDI) in the Knowledge Dimension in 2023. The method used in this research is qualitative. Data collection techniques use observation, interviews, documents and audiovisual and digital materials. The research time was 9 months. The results of the analysis of the Singkawang City Government's strategy in increasing the HDI in the Knowledge dimension in 2023 consist of 5 (five) aspects or stages, there are namely: Purpose (objective), Environments (environment), Directions (direction), Actions, and Learnings.